Pemanfaatan Web Service Sebagai Integrasi Data Farmasi di RSU Banyumas - Arif Adi; Riyanto Riyanto (JUITA : Jurnal Informatika, 2013)
This research aims to design build web services as data integration on Pharmacy RSU Banyumas using simple object access protocol method. This research was conducted with the stages of planning, analysis, design, implementation, testing and evaluation. Web services is a new paradigm in implementing distributed systems over the web using XML technology base with standard HTTP and SOAP protocols. Given the open-standard support technologies used in web services, the web services implementation is promising a lot of conveniences and improvements in support of the integration of a wide range of system platforms and applications, either through internet or intranet infrastructure or extranet. The result of this research is harmonious web services using simple object access protocol that provides the pharmaceutical information system solution without having to build new applications with web services as data integration